2017
DOI: 10.5964/ejop.v13i2.1250
|View full text |Cite
|
Sign up to set email alerts
|

Using a computer simulation to improve psychological readiness for job interviewing in unemployed individuals of pre-retirement age

Abstract: Unemployed individuals of pre-retirement age face significant challenges in finding a new job. This may be partly due to their lack of psychological readiness to go through a job interview. We view psychological readiness as one of the psychological attitude components. It is an active conscious readiness to interact with a certain aspect of reality, based on previously acquired experience. It includes a persons’ special competence to manage their activities and cope with anxiety. We created Job Interview Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A previous study has revealed that VR job-interview training is beneficial for neurotypical individuals who have been unemployed for more than one year (Aysina, Maksimenko, & Nikiforov, 2016). The anecdotal survey findings from the Inclusive Spectrum Exhibition confirm the interest of neurotypical individuals in using an app (VR/VM Job Interview Training of individuals with ASD: Inclusive Spectrums, 2020).…”
Section: And If It [Referring To An App] Also Includes Examples Of Ki...mentioning
confidence: 73%
“…A previous study has revealed that VR job-interview training is beneficial for neurotypical individuals who have been unemployed for more than one year (Aysina, Maksimenko, & Nikiforov, 2016). The anecdotal survey findings from the Inclusive Spectrum Exhibition confirm the interest of neurotypical individuals in using an app (VR/VM Job Interview Training of individuals with ASD: Inclusive Spectrums, 2020).…”
Section: And If It [Referring To An App] Also Includes Examples Of Ki...mentioning
confidence: 73%
“…Researchers also have developed evidence-based interventions focused on job-interview simulation training (Aysina et al, 2016), career decision making (Bullock-Yowell et al, 2014), goal orientation (van Hooft & Noordzij, 2009), and self-confidence (Hillman & Knill, 2018). In addition, Wanberg and colleagues (2020b) designed an online networking intervention (Building Relationships and Improving Opportunities; BRIO) to support unemployed individuals by enhancing their networking skills and options (i.e., using existing or new social contacts to find work and obtain instrumental support for their job applications), which demonstrated positive effects on networking self-efficacy and the quality of re-employment (Wanberg et al, 2020b).…”
Section: Existing Unemployment Interventions: Why a New Paradigm Is N...mentioning
confidence: 99%
“…Young people experience difficulties transitioning into adulthood and from education to work (Grosemans et al, 2018), however, they are more likely to rely on family support (Jacob, 2008;Kilpatrick & Trew, 1985;McKee-Ryan et al, 2005). Older people in pre-retirement age could struggle more searching for a new job (Aysina et al, 2017), and feel relatively more deprived being unemployed (Stynen et al, 2015), but they tend to have accumulated more wealth and savings (Weller & Wenger, 2019). Finally, the middleaged group is likely to be burdened by family responsibilities the most, as it is expected to capture most of the sandwich generation, who need to take care of their parents and their children simultaneously (Boyczuk & Fletcher, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…At the practical level, some re-employment initiatives have already shown positive results for older unemployed individuals. For example, Aysina et al (2017) tested the effectiveness of a job interview simulation training (i.e., a computer-based simulator, which allowed unemployed job seekers at the preretirement age to practice interviewing), and found that those participants who followed the training showed decreased heart-rate and increased psychological readiness after the training and in comparison with a control age group. Similarly, Rife and Belcher (1994) showed that participation in Job Club intervention programmes helped pre-retirement age individuals get re-employed.…”
Section: Practical and Policy Implicationsmentioning
confidence: 99%